PENGARUH TERAPI MUSIK KLASIK TERHADAP PENURUNAN TEKANAN DARAH PADA LANSIA DENGAN HIPERTENSI DI KELURAHAN SIMPANG RUMBIO WILAYAH KERJA PUSKESMAS KTK KOTA SOLOK - Netty Herawati, Kurniati Maya Sari.,WD Armanda Tri MurtiNingsih (LPPM Universitas Muhammadiyah Sumatera Barat, 2018)
Old age is the age at which risk of degenerative diseases such as hypertension.Hypertensive disease if not treated immediately can be fatal to the sufferer, one of theefforts to lower blood pressure in people with hypertension by doing music therapy. Musicis able to clear the mind and the sound of music is able to create physical forms that affectour health, awareness, and everyday behavior. The power of music that is a powerfulsource of emotional healing to ward off negative forces and increase positive power. Thepurpose of this research is to know the blood pressure before and after being given musictherapy in elderly with hypertension in Working Area of Puskesmas KTK Kota Solok. Thisresearch design is quasi experiment with One group pretest post test design with 18samples with Purposive sampling technique. The result showed that the difference of bloodpressure before and after classical music therapy in elderly with mild hypertension wasobtained p-value = 0,001 (<0,05), in elderly with moderate hypertension, p-value = 0,023(<0,05 ). This number indicates that there is influence between systolic blood pressurebefore and after classical music therapy whereas in severe hypertension we get p-value =0,175 (˃0,05). This figure shows that there is no influence between systolic blood pressurebefore and after classical music therapy.Keywords :music theraphy, elderly, hypertension, blood pressure.